Ratio-independent prey preferences by an estuarine mysid. (15th May 2020) - Froneman, P William; Cuthbert, Ross N
Abstract: The present study quantified prey preferences by adult males and females of the mysid Mesopodopsis wooldridgei fed the calanoid copepods Pseudodiaptomus hessei and Paracartia longipatella at varying proportions. Both sexes of M. wooldridgei showed a lack of prey switching and a strong preference for the smaller, less active P. longipatella irrespective of density. Given a lack of low-density prey refuge, this finding may have important implications for the distribution of P. longipatella in estuaries along the eastern seaboard of South Africa. Results of the present study contribute to a growing body of literature that suggests that selective predation may play an important role in structuring plankton prey populations in shallow water ecosystems.